Early Childhood Care and Education in India: Challenges and Enablers in Ensuring Quality Early Childhood Education in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The progressions in the social and monetary construction of India have increased the requirement for widespread early childhood education. The imposing difficulties before the Indian Government are to give great early childhood education programs to save native practices like multilinguality, familylocal area association, support of more established youngsters as caretakers of their more youthful kin and to give early childhood education to all kids regardless of genuine monetary imperatives. Various drives have been taken by the Government of India for acquiring quality the type of strategies, plans, protected revisions, acts, advancement of value norms and educational plan system, plans and leader programs like Integrated Child Development Services (ICDS) District Primary Education Program (DPEP) and Sarva Shiksha Abhiyan (SSA). In this undertaking, some place India has compromised with the non-debatable quality guidelines for ECCE, driving the rise of expected and surprising issues and difficulties. Thus, the nation has missed the objective of guaranteeing quality in ECCE. In any case, late examinations give proof of huge advancement towards quality changes. Obviously, there are low accomplishments in certain angles and in certain locales, yet additionally improvement in others which shows that guaranteeing quality is an achievable objective. This paper expects to depict drives of the Government of India, survey the ground real factors, recognize significant difficulties in quality change in ECCE and recommend conceivable empowering agents to connect something very similar.